PROOF OF THE CRIME OF MURDER REGARDLESS OF THE USE OF FORENSIC AUTOPSY EVIDENCE (Kendari District Court Study) - Irmansah, Irmansah; Satria, Hariman; Dagani, Gamlan (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
In essence, evidence in criminal cases is an effort to provide evidence through tools that can prove a case and its allegations, one of which is forensic autopsy evidence which is used as evidence. In fact, forensic autopsy evidence is very important in criminal homicide cases because it can confirm a person's death carried out by a forensic autopsy expert and speed up the court process. The aim is to prove the KUHAP evidentiary system through forensic evidence, and determine the value of forensic evidence in murder, and use it as expert testimony, this is also used as a basis for the judge's decision against the defendant. The research carried out is empirical legal research using an empirical approach from secondary data by managing primary, secondary and tertiary legal materials. Based on the research results, first we have to know that every country definitely has laws or regulations that apply in each country. As in murder cases, if witness statements are not always correct, judges really need forensic autopsy evidence as expert testimony, and it is rare to find witnesses who directly witnessed the crime of murder, and this becomes an obstacle for judges. Then in murder cases, many families do not want to have a forensic autopsy done. The meaning of a forensic autopsy is to find the true case and look for the causes that caused the person's death. Then, for clues and truth, a forensic autopsy must be carried out to achieve justice.